Academic Stress May Contribute to the Onset of Pediatric Inflammatory Bowel Diseases. Issue 4 (October 2018) - Krishna, Mahesh Z.; Barton, Keisha R.; Perez, Carla M.; Walsh, Seema M.; Assa, Amit; Kellermayer, Richard
Abstract : ABSTRACT: It is currently unclear whether seasonality affects the onset of inflammatory bowel diseases (IBDs: Crohn disease and ulcerative colitis) in children. Here, we examined the records of pediatric patients with IBD diagnosed between 2009 and 2015 in a discovery cohort of 169 cases and a validation cohort of 122 subjects, where the month of symptoms onset could be determined. No seasonal patterns could be identified in respect to conception, birth, and disease onset. An annual rhythm of symptomatic onset, however, correlating with academic semesters was identified. IBD symptoms in the discovery cohort presented significantly more ( P = 0.0218) during 5 months including the initiation (August, September, January) and the termination of academic semesters (December, May) compared to any other 5 months of the year. This observation was validated in the independent cohort ( P < 0.0001). Our findings imply that academic stress may contribute to disease onset in pediatric IBD, which may improve timely diagnosis. Abstract : Supplemental Digital Content is available in the text